A Synthetic Biology Perspective on the Bioengineering Tools for an Industrial Microalga: Euglena gracilis - Chen, Zhenfan; Zhu, Jiayi; Du, Ming; Chen, Zixi; Liu, Qiong; Zhu, Hui; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena is a genus of single-celled eukaryotes that show both plant- and animal-like characteristics. E. gracilis, as a model species in the genus of Euglena, is of significant scientific value for studying endosymbiosis and chloroplast development. Its cells contain many high-value products, including vitamins, amino acids, pigments, unsaturated fatty acids, and carbohydrate paramylon as metabolites. As an industrial species, E. gracilis is also of primary biotechnological and economic importance as high value-added foods, medical, and cosmetic, as well as high-quality feedstock for jet-fuel production. For more than half a century, E. gracilis has been an industrial biotechnology platform for fundamental biology research, and mainly physiological and biochemical methods explored relevant studies. Although many researchers focused on genetic engineering tools for E. gracilis in recent years, little progress has been achieved due to the lack of high-quality genome information and efficient techniques for the genetic operation. This article reviewed the progress of the genetic transformation of E. gracilis, including methods for the delivery of the exogenous materials and other advanced biotechnological tools for E. gracilis, such as CRISPR and RNA interference. We hope to provide a reference to improve the research in functional genomics and synthetic biology of Euglena.